Prognostic relevance of hemodialysis for short-term survival in patients after LVAD implantation - Schmack, Bastian; Grossekettler, Leonie; Weymann, Alexander; Schamroth, Joel; Sabashnikov, Anton; Raake, Philip; Popov, Aron F.; Mansur, Ashham; Karck, Matthias; Schwenger, Vedat; Ruhparwar, Arjang (Scientific reports, 2018)
End-stage heart failure (HF) is associated with renal failure (RF). This study aimed to determine the prognostic influence of RF and post-operative hemodialysis on short-term survival following left ventricular assist device (LVAD) implantation. This retrospective study includes 68 patients undergoing LVAD treatment. Kidney function was recorded prior to LVAD implantation, immediately afterwards and after 30 days, noting the need for hemodialysis. Median pre-operative Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) classification was 3.47 ± 1.08. 30 days after implantation there was a significant improvement of estimated glomerular filtration rate (eGFR) and reduction of blood urea nitrogen (BUN). Of pre-operative RF parameters, BUN was associated with increased mortality and need for early post-operative hemodialysis. Post-operative hemodialysis was associated with significantly lower short-term survival, while pre-operative hemodialysis did not impact mortality. Post-operative acute kidney injury (AKI) requiring hemodialysis can be regarded as a strong negative prognostic marker for short-term survival. The absence of a clear correlation between most routine RF parameters and survival or the need for early post-operative hemodialysis calls into question the predictive value of pre-operative RF. The negative association of only post-operative hemodialysis on short-term survival emphasises the impact of the occurrence of AKI.